Urbanus MERAWAT KEBHINEKAAN: DIALOG INTERRELIGIUS SEBAGAI UPAYA MEMBANGUN TOLERANSI DAN KERUKUNAN UMAT BERAGAMA: MERAWAT KEBHINEKAAN: DIALOG INTERRELIGIUS SEBAGAI UPAYA MEMBANGUN TOLERANSI DAN KERUKUNAN UMAT BERAGAMA - Sila, Urbanus (Institut Agama Kristen Negeri Toraja, 2024)
Abstract: The focus of the discussion is on Caring for diversity: interreligious dialog as an effort to build tolerance and religious harmony. Indonesia, with its rich culture, is inhabited by people of various ethnicities, religions and races. This diversity is a strength, but it can also be a potential conflict. Interreligious dialogue is important to build tolerance and religious harmony. This article analyzes the role of interreligious dialogue in maintaining Indonesia's diversity. This discussion uses a qualitative method with a literature study. Data were collected from books, scientific journals, and online articles that discuss interreligious dialog and tolerance. The previous literature is discussed using the technique of analyzing the discussion on the text. The results of the discussion show that interreligious dialog has an important role in building tolerance and religious harmony. Interreligious dialogue can help build mutual understanding, respect for differences, and cooperation between religious communities. Interreligious dialog can also help resolve conflicts between religious communities. This research recommends that interreligious dialog continue to be carried out and strengthened. Interreligious dialog needs to involve all stakeholders, including the government, religious leaders and civil society. Interreligious dialog also needs to be carried out at various levels, from the national level to the local level. Abstrak: Fokus pembahasan tentang Merawat kebhinekaan: dialog interreligius sebagai upaya membangun toleransi dan kerukunan umat beragama. Indonesia, dengan kekayaan budayanya, dihuni oleh masyarakat yang beragam suku, agama, dan ras. Keberagaman ini merupakan kekuatan, namun juga dapat menjadi potensi konflik. Dialog interreligius menjadi penting untuk membangun toleransi dan kerukunan umat beragama. Artikel ini dianalisis peran dialog interreligius dalam merawat kebhinekaan Indonesia. Pembahasan ini menggunakan metode kualitatif dengan studi literatur. Data dikumpulkan dari buku, jurnal ilmiah, dan artikel online yang membahas tentang dialog interreligius dan toleransi. Literatur terdahulu dibahas dengan menggunakan teknik analisis pembahasan pada teks. Hasil pembahasan menunjukkan bahwa dialog interreligius memiliki peran penting dalam membangun toleransi dan kerukunan umat beragama. Dialog interreligius dapat membantu membangun saling pengertian, menghormati perbedaan, dan kerjasama antarumat beragama. Dialog interreligius juga dapat membantu menyelesaikan konflik antarumat beragama. Penelitian ini merekomendasikan agar dialog interreligius terus dilakukan dan diperkuat. Dialog interreligius perlu melibatkan semua pemangku kepentingan, termasuk pemerintah, tokoh agama, dan masyarakat sipil. Dialog interreligius juga perlu dilakukan di berbagai tingkatan, mulai dari tingkat nasional hingga tingkat lokal.